Articulação temporomandibular: anatomia, dinâmica e disfunções temporomandibulares - Santos, Nídia Cristina Castro dos [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This study gathered some of the most relevant researches already undertaken regarding the Temporomandibular Joint, presenting descriptions of its anatomy and dynamics, and relating them to the main aspects of joint dysfunctions. Literature recognizes that the Temporomandibular Joint, responsible for lower jaw movements, comprehends the skull base and the jaw bone. Its anatomy and dynamics are of great importance in order to understand the functions of Stomatognathic System as well as to study Temporomandibular Joint Dysfunction. The elements that compose this synovial joint and the bilateral characteristic confer eminent importance to the ATM before the skeleton head, the ability to perform broad movements and high complexity in its operation. It is accepted that the overload of one anatomical structure from the TMJ or other components of the Stomatognathic System leads to Temporomandibular Joint Dysfunctions. These disorders have different etiologies, ranging from malocclusion to emotional stress, and various forms of treatment, which are related in this study

O presente estudo reuniu alguns dos mais relevantes trabalhos já realizados a respeito da articulação temporomandibular, apresentando descrições de sua anatomia e dinâmica, e relacionando-as com os principais aspectos das disfunções articulares. A literatura reconhece que a articulação temporomandibular, responsável pelos movimentos mandibulares, é compreendida pela base do crânio e osso da mandíbula. Sua anatomia e dinâmica são de grande importância para a compreensão das funções do sistema estomatognático, bem como para o estudo das disfunções temporomandibulares. Os elementos que compõem esta articulação sinovial e sua característica de bilateralidade conferem à ATM grande importância perante o esqueleto cefálico, capacidade de realização de amplos movimentos e alta complexidade em seu funcionamento. É aceito que a sobrecarga de uma de suas estruturas anatômicas ou de outros componentes do sistema estomatognático leva às disfunções temporomandibulares. Estas disfunções possuem diferentes etiologias, abrangendo desde má oclusão a estresse emocional, e diversas formas de tratamento, os quais são relacionados neste estudo
Keywords: Articulação temporomandibular; Movimentos mandibulares; Disfunção temporomandibular